2019
DOI: 10.1002/chem.201903362
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Computational Studies for Pd‐NHC‐Catalyzed Amination with Primary Alkylamines and Secondary Anilines: Rationalizing Selectivity for Monoarylation versus Diarylation with NHC Ligands

Abstract: The relative rates of arylation of primary alkylamines with different Pd-NHCcatalysts have been measured, as have the relative rates of arylation of the secondary aniline product in an attemptt ou nderstand the key ligand design features necessary to have high selectivity for the monoarylated amine product. As the substituents on the N-aryl ring of the NHC increaseinsize, selectivity for monoarylation increases and this is furthere nhanced by chlorinating the back of the NHC ring. Computations have been perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The elimination of KBr (precipitation) from C to D and the elimination of CO (gas evolution) from D to E are irreversible processes, both of which can exit the system. Similar uphill but irreversible pathway with the generation of insoluble salt has also been proposed in the palladium-catalysed Buchwald–Hartwig amination by Organ et al 20 The results of the calculated energy for the final product ( E ) were found to be −8.0 kcal mol −1 and that the most unstable level, that is the transition state toward iron hydride, was +23.0 kcal mol −1 . Although the systems calculated in this study have been partially simplified to reduce the steric requirements ( e.g.…”
Section: Resultssupporting
confidence: 75%
“…The elimination of KBr (precipitation) from C to D and the elimination of CO (gas evolution) from D to E are irreversible processes, both of which can exit the system. Similar uphill but irreversible pathway with the generation of insoluble salt has also been proposed in the palladium-catalysed Buchwald–Hartwig amination by Organ et al 20 The results of the calculated energy for the final product ( E ) were found to be −8.0 kcal mol −1 and that the most unstable level, that is the transition state toward iron hydride, was +23.0 kcal mol −1 . Although the systems calculated in this study have been partially simplified to reduce the steric requirements ( e.g.…”
Section: Resultssupporting
confidence: 75%
“…It is important to note that [(NHC)­PdCl 2 ] 2 can also act as a precatalyst to generate [(NHC)­Pd(0)], but it is less active than the PEPPSI-type complexes; although there have not been enough control experiments. Because of space limitation, the published work in this area has not been covered in detail; the interested reader should consult the relevant reviews and book chapters for further insight into this area. , …”
Section: Synthesis and Applications Of L1pd(0) Precatalystsmentioning
confidence: 99%
“…More recently, the effects of biaryl phosphines, ylide-substituted phosphines, and meta-terarylphosphine ligands were computationally evaluated by Baik, , Ma, Gessner, and Jong and Lim groups, respectively. The mechanism for Pd–NHC-catalyzed C–N coupling was also recently analyzed . The general mechanism is generally divided into four main steps (Figure ): (i) oxidative addition of the aryl halide, (ii) amine coordination, (iii) amine deprotonation and halide release, and (iv) reductive elimination.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for Pd−NHCcatalyzed C−N coupling was also recently analyzed. 44 The general mechanism is generally divided into four main steps (Figure 2): 45−51 (i) oxidative addition of the aryl halide, (ii) amine coordination, (iii) amine deprotonation and halide release, and (iv) reductive elimination.…”
Section: ■ Introductionmentioning
confidence: 99%